The stock identification of the Cape horse mackerel, Trachurus trachurus capensis (Pisces: Carangidae) - Naish, Kerry-Ann (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1990)
Three stocks of the Cape horse mackerel, Trachurus trachurus capensis, have been recognised in the ICSEAF convention region off southern Africa (Figure 1) on the basis of catch distribution and biological analyses. They were identified as being off Namibia (ICSEAF Divisions 1 . 3 and 1.4), off the West Coast of South Africa (Div. 1.6) and off the South Coast (Div. 2.1 and 2.2). Recently, speculation as to the accuracy of the classification of the South African populations has arisen. The aim of this study was to determine the number of stocks In Divisions 1.6, 2.1 and 2.2, using methodology which assessed the spatial and temporal nature and the phenotypic and genotypic characteristics of the species. The distribution of horse mackerel was evaluated by studying the trends in catch data and length frequency distributions obtained from the demersal industry during 1986 to 1988 and from the demersal biomass cruises in 1987 and 1988. Adult fish, found in Div. 2.1 and 2.2, probably migrated; during the months in which horse mackerel were expected to spawn, CPUE values were higher over the central Agulhas Bank than in the east of the study region. During the quiescent period, catches and numbers were higher in the latter region. Juvenile horse mackerel were found in the nursery areas utilised by pelagic fish and it is likely that they were transported northward from the Agulhas Bank. A decrease in biomass of individuals in Div. 1.5 indicated a separation between a northern and a southern population. Analyses of the phenotype, or epigenetic characters, of horse mackerel were used as a further test of stock integrity. Monthly samples were drawn from Div. 1.6, 2.1 and 2.2 during May 1988 to June, 1989. Comparisons for the values obtained from growth, length-at-50%-maturity and the season of otolith ring formation from each region showed no significant variation in the phenotype. Morphometric analysis proved inconclusive. Monthly gonadosomatic indices show that fish south of the Orange River share the same spawning season. Reports from the literature show that horse mackerel in the latter region differ from those of northern Namibia in spawning season, age-at-50%-maturity and season of otolith ring formation. The genetic structure of the populations of horse mackerel was evaluated by means of a restriction enzyme analysis of the Mitochondrial DNA of 37 fish collected from Divisions 1.4, 1.5, 1.6, 2.1 and 2.2. Two composite genotypes of horse mackerel were found; one belonging to fish in Div. 1.4 and one to fish in Div. 1.6, 2.1 and 2.2. The genetic distance between the two genotypes, 0.07, was the expected distance between two populations at a subspecies level. Fish in Div. 1.5 consisted of both genotypes and may be a region of mixing between the two populations. The interpretation of results was cautioned; prevlous work has shown that the migration of a small number of individuals between two stocks can be expected to maintain a low variation between the populations. In concluding, it was recommended that the horse mackerel be managed as two stocks, one in Div. 1.3 and 1.4 and one in Div. 1.6, 2.1 and 2.2
Keywords: Carangidae -- Identification; Trachurus trachurus -- Identification; Carangidae -- South Africa; Trachurus trachurus -- South Africa